Experimental investigation of ultrasonic vibration-assisted cryogenic minimum quantity lubrication for milling of Ti-6Al-4V and grinding of Zerodur - Blasl, Jacqueline; Lichtinger, Klaus; Vieltorf, Fabian; Zaeh, Michael F.; Hanenkamp, Nico (Production Engineering, 2023)
Increasing demands on component properties are leading to the development of high-performance materials for which conventional production methods are reaching their limits from an economic and ecological point of view. In recent years, two technologies have been developed that show great potential compared to conventional machining processes, particularly in machining high-performance materials such as the titanium alloy Ti-6Al-4V. Ultrasonic-assisted machining leads to reduced cutting forces and increased tool life. Cryogenic minimum quantity lubrication prevents the occurrence of high machining temperatures and allows higher material removal rates without a negative impact on tool life. This paper shows the influence of ultrasonic-assisted milling and grinding processes in combination with cryogenic minimum quantity lubrication on the machinability of the high-strength materials Ti-6Al-4V and Zerodur. The investigation addressed cutting forces, tool wear, and surface roughness. The superposition of the technologies resulted in longer tool life and lower tool wear for both milling and grinding. However, the surface roughness was consistently higher due to the ultrasonic superposition. Nevertheless, machining with ultrasonic vibration-assisted cryogenic minimum quantity lubrication has great potential for difficult-to-machine materials, especially due to the reduction in tool wear.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Cryogenic cooling; Minimum quantity lubrication; Ti-6Al-4V; Ultrasonic vibration; Vibration-assisted machining; Zerodur

Grundstein für neuartige Bearbeitungsstrategie gelegt - Blasl, Jacqueline; Vieltorf, Fabian; Hanenkamp, Nico; Zaeh, Michael (VDI-Z Integrierte Produktion, 2021)
Bei neuartigen Werkstoffen stoßen herkömmliche Fertigungsverfahren aus ökonomischer und ökologischer Sicht an ihre Grenzen. In Forschungsprojekten werden derzeit die Ultraschallbearbeitung und die kryogene Minimalmengenschmierung (kMMS) betrachtet, die sich bei schwer zerspanbaren Werkstoffen gegenüber konventionellen spanabhebenden Verfahren auszeichnen. Im Verbundprojekt „KryoSonic“ wird die Überlagerung beider Technologien bei Fräs- und Schleifprozessen untersucht.<br

Superposition of cryogenic and ultrasonic assisted machining of Zerodur - Vogt, C.; Thiess, H.; Blasl, Jacqueline; Hanenkamp, Nico; Lichtinger, K. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
Cryogenic machining is a cooling strategy that has recently been frequently found in research in machining processes for materials such as inconel or titanium. In particular it is reported that these processes are more efficient in terms of tool life and material removal rate compared to those with water-based cooling lubrication. An increase in efficiency and productivity has significant potential from a cost perspective, especially when grinding Ceramic Matrix Composite materials and similar. These processes are used, for example, in the lightweighting of telescope mirrors made of e.g. fiber-reinforced silicon carbide, or Zerodur. An increase in productivity would be clearly noticeable in the manufacturing costs due to normally long machining times. In the "KryoSonic" project, we investigated whether and to what extent the use of cryogenic machining affects the rough machining of Zerodur with and without ultrasonic support.
CRIS-Team Scopus Importer:2023-11-17
Keywords: brittle chipping; cryogenic machining; Grinding; ultrasonic